Mengasah Ilmu Digital Marketing Lewat Program Studi Independen MSIB Batch 6 di NF Academy - Safina Nur Tyas Utami (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
In today's technological developments, changes towards digital in the industrial sector require us to always be adaptive to change. The reason is that the current marketing is digital-based marketing or what is usually called digital marketing. For this reason, the Ministry of Education, Culture, Research and Technology (Kemendikbud Ristek) initiated an Independent Campus program, one of which is called Certified Independent Study and Internship (MSIB) as an answer to preparing the Indonesian generation to be ready to face the challenges of the era of digitalization. For this reason, the right step in facing these changes as a student is to take part in a training program that suits your interests in preparing for a career in the digital marketing field.